2018
DOI: 10.14744/hnhj.2018.60565
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating corneal changes in patients with Aort aneurysm

Abstract: Introduction: To evaluate corneal changes in patients with aortic aneurysm. Methods: The study group (Group 1) included 63 eyes of 33 patients diagnosed with aortic aneurysm and the control group (Group 2) included 69 eyes of 35 healthy people who presented at the Ophthalmology Department. Complete ophthalmologic examination was performed and steepest keratometry measurements were taken via rotational Scheimpflug corneal tomography on the following parameters: sagittal curvature map (S steepest), central corne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…An association between KC and mitral valve prolapse has been assumed since the 1980s, and a recent meta-analysis, including six studies, indeed found a significant coexisting prevalence between KC and mitral valve prolapse [75]. Back difference elevation measured by Scheimpflug corneal tomography was found to be significantly higher in patients with aortic aneurysm, suggesting a link between aortic aneurysm and KC [76].…”
Section: Discussionmentioning
confidence: 97%
“…An association between KC and mitral valve prolapse has been assumed since the 1980s, and a recent meta-analysis, including six studies, indeed found a significant coexisting prevalence between KC and mitral valve prolapse [75]. Back difference elevation measured by Scheimpflug corneal tomography was found to be significantly higher in patients with aortic aneurysm, suggesting a link between aortic aneurysm and KC [76].…”
Section: Discussionmentioning
confidence: 97%